Management of spontaneous cerebrospinal fluid leakage: A surgical case series - Amrou Abdelrahman; Joshua C. Bizilis; Scott Davies; Arul Bala (Interdisciplinary Neurosurgery, 2022)
Background: The pathophysiology and optimal management of spontaneous cerebrospinal fluid (CSF) leakage is poorly understood. Here, we present a case series of 36 patients who underwent surgical management of spinal CSF leakage with discussion of different surgical approaches to treat different pathological types of spinal CSF leak. Methods: All patients who underwent surgical management of spinal CSF leakage at two neurosurgical units in Western Australia under the care of a single consultant surgeon from April 2017 were included. Descriptive patient data was retrospectively collected from the medical records, imaging reports and operation notes. Our approach, diagnostic imaging algorithm, surgical methods, and complications are presented. Results: Thirty-six patients were managed surgically from April 2017 – 2021. The median age was 47 years (range; 24–79) with 66 % being female. Regarding pathological culprit, eighteen patients (50 %) had a confirmed CSF leak due to a dural tear, 5 (13 %) a meningeal diverticulum, 2 (5.5 %) a Tarlov cyst and 1 (2.7 %) CSF-venous fistula. Ten patients (27 %) had no spinal CSF leak or dural defect found intraoperatively, despite having positive diagnostic criteria andpositive findings on pre-op imaging scans. In terms of location of pathology, four patients (11 %) underwent cervical level surgery, 27 (75 %) thoracic, 2 (5.5 %) thoracolumbar and 3 (8.3 %) lumbar. Post-operative imaging was available for 26 (72 %) patients, twenty-three (88 %) showed complete resolution of signs of SIH and/or extradural CSF collections, and three (10 %) had MRI spines showing ongoing extradural CSF collections. Thirty patients were contacted for long term follow up, with eighteen (60 %) classified as having good response based on a HIT-6 score less than 50, eight patients (27 %) having partial response and four patients (13 %) having poor response. Four patients (11 %) had non-neurological postoperative complications managed successfully. Conclusion: A systematic multidisciplinary approach between interventional neuroradiology and neurosurgery is crucial for assessment of patients with a suspected CSF leak. This approach facilitates timely diagnosis, selection of interventional candidates versus surgical candidates, and improved patient outcomes. In this paper we present our case series which utilises our diagnostic algorithm and individualized surgical approaches based on the pathology and anatomical location of spinal CSF leak.